ANALISIS PENGARUH TINGKAT PENDIDIKAN DAN TINKAT UPAH TERHADAP TINGKAT PARTISIPASI ANGKATAN KERJA DI KOTA PEKANBARU MENURUT JENIS KELAMIN - Indra, Putra Maika; Yusni, Maulida; Hilmah, Zuryan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study aims to analyze the level of education and the level of wages to level of labor force participation in Pekanbaru by gender. The data used in this study uses primary data. Primary data were obtained using a questionnaire, with a labor force participation of 494,362 people, with a men labor force of 292,569 people (60%) and women of 194,793 people (40%). Samples were taken randomly based on the Slovin formula which involved 100 respondents consisting of 60 male laborforce and 40 female laborforce.This research uses descriptive and quantitative research types. The analytical method used is multiple linear analysis. Based on the results of the study, the level of education does not affect the level of male labor force participation and the level of wages partially affects the level of male labor force participation. The level of wage is the most dominant variable effects the level of male labor force participation. The level of education partially affects the level of female labor force participation and the level of wages does not affects the level of female labor force participation in Pekanbaru. The level of education is the most dominant variable effects the level of female labor force participation.Keywords: level of labor force participation, level of education, level of wage